A Novel Approach for Detection of Single and Collaborative Black Hole Attacks in MANET. (2016) - Arathy, K.S.; Sminesh, C.N.
Abstract: Ad hoc On Demand Distance Vector Routing is an extensively accepted routing protocol for Mobile Ad hoc Network. The inadequacy of security considerations in the design of AODV makes it vulnerable to black hole attack in which, malicious nodes attract data packets and drop them instead of forwarding. Among the existing black hole detection schemes, just a few strategies detect both single and collaborative attacks and that too with much routing, storage and computational overhead. In this paper, we propose a novel strategy to detect single and collaborative black hole attacks, with reduced routing and computational overhead. The proposed D-MBH algorithm detects single and multiple black hole nodes using an additional route request with nonexistent target address, computes a threshold ADSN, creates a black hole list and invokes the proposed D-CBH algorithm. Using ADSN, black hole list and next hop information extracted from RREP, the D-CBH algorithm creates a list of collaborative black hole nodes.